Digital Technologies: A Congregating pan-African Public Management on the Fourth Industrial Revolution for Employability and Sustainable Growth - Atianashie, Miracle; Adaobi , Chukwuma Chinaza; Adinkrah-Appiah, Kwadwo; Obeng-Ofori , Daniel (Universitas Pendidikan Ganesha, 2024)
The Fourth Industrial Revolution (4IR) is the concept of blurring the real world with the technological world and it is characterized by a range of new technologies that are fusing the physical, digital, and biological worlds. The study analyze the state of pan-African public administration practice within the praxis of the Fourth Industrial Revolution (4IR) to enhance employability and sustainable development. The 4IR is the concept of blurring the real world with the technological world, and a range of new technologies that are fusing the physical, digital, and biological worlds characterizes it. At its core, the 4IR is driven by the convergence of physical and digital technologies. It is the current developing environment in which disruptive technologies and trends such as the Internet of Things (IoT), robotics or intelligent robots, mobile supercomputing, virtual reality (VR), and artificial intelligence (AI) are changing the way people live and work. Furthermore, the study interrogates the contentious and contemporary potentials of the pan-African public administration vis-à-vis the fourth industrial revolution as we draw closer to the future. The study employed a descriptive research design, relying on content analysis. A secondary source of data collection was employed. Some of the significant findings include sustainable development, Employability, and Fourth Industrial Revolution. The study advocates that for African public administration to be relevant to the governance and sustainable development needs of the continent, it must restructure its educational curriculum to take advantage of the benefits that the technological advancement of the fourth industrial revolution provides.